Introduction [in The road to the WTO twelfth Ministerial Conference: A Latin American and Caribbean perspective] - Campos, Adriana; Piñeiro, Valeria; Piñeiro, Martín (Instituto Interamericano de Cooperación para la Agricultura, 2021)
In December 2017 the WTO Ministerial Conference was held in Buenos Aires, Argentina. They were difficult times both in terms of economic and political uncertainties. The global economy was faltering and there was growing dissatisfaction with globalization and the global trading regulatory system had already surfaced and affected the spirit and environment in which negotiations in the multilateral trading system took place. Consequently, it also affected the deliberations in the Conference and the possibilities to attain progress in the themes that where under consideration like, such as a plurilateral agreement on fisheries and an agreement on public food stockholdings.